Unmasking financial psychopaths : inside the minds of investors in the twenty-first century - Gregory, Deborah W.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Unmasking Financial Psychopaths explores three unrelated - yet crucial - factors that have contributed to the rise of'financial psychopaths' in society and what this means for financial consumers.
Keywords: Science